Rare ocular manifestations in an 11-year-old girl with incomplete Kawasaki disease: A case report. Issue 22 (June 2018) - Gao, Yunxia; Zhang, Yifan; Lu, Fang; Wang, Xiaoyue; Zhang, Ming
Abstract: Introduction: Kawasaki disease is a necrotizing vasculitis featuring fever, erythema, conjunctivitis, and lymphadenopathy. Ocular manifestations in Kawasaki disease are commonly limited to anterior segment, posterior segment lesions are rarely reported. Case presentation: We report a unique case of ocular manifestations in an 11-year-old girl with incomplete Kawasaki disease. An 11-year-old Asian girl presented with severe enophthalmos, retinitis, retinal detachment, and choroidal detachment secondary to an unexplained fever for 10 days. Conclusion: To the best of our knowledge, this is the first documented case of incomplete Kawasaki disease with severe posterior segment lesions. The local use of dexamethasone in the eye was effective in our patient. Surgical intervention might not be necessary even though the initial symptoms could be devastating. The eye should be monitoring the eye routinely in patients with Kawasaki disease.